Система автоматизації теплиці для сільськогоспо дарської діяльності - Цубера, М. С. (ХНУРЕ, 2025)
In project suggests a solution of automatization of monotonous work, in order to save people's time and energy. There will also be the opportunity to conduct experiments to find the best conditions for a particular plant. It can be used not only for agricultural purposes, but with enough skills it can be remade for other demands.
Keywords: автоматизація теплиці; сільськогосподарська діяльність